My Brilliant Friend: Drawing the Profile of a Transnational Interpretative Community - Farinacci, Elisa; Bisoni, Claudio (Cinergie – Il Cinema e le altre Arti, 2020)
The article focuses on the international reception of the first season of the TV series L’amica geniale (My Brilliant Friend, 2018-). This Italian media product has been distributed and circulated in numerous countries around the globe as the television adaptation of the first book of Elena Ferrante’s bestselling Neapolitan Novels. Generally, the forms of representation and narration of Italianness in Italian TV series that circulate abroad present two distinctive traits: on the one hand, they feature a globally recognizable image of Italian identity and culture, and on the other hand, they narrate stories that are deeply rooted in Italian local contexts. L’amica geniale places in the middle of this spectrum. The aim of this article is to discuss how the audience of the tv series contributes to defining its identity as a transnational/Italian cultural product by fostering symbolic processes often in tension with each other. L’amica geniale appeals to the foreign public both due to its local features, that is, by presenting elements that can be easily traced back to Italian history and culture, and because it can be inscribed within the broad label of quality tv.